Preconcentration of heavy metals ions from aqueous solutions by means of cellulose phosphate: An application in water analysis - De Magalhães Padilha, P. [UNESP]; Rocha, J. Cesar [UNESP]; Moreira, J. Celso [UNESP]; De Sousa Campos, J. Theodoro [UNESP]; Do Carmo Federici, C. [UNESP] (Elsevier, 1997)
Cellulose phosphate (CELLPHOS) was studied as a collector for analytical preconcentration of traces of Cd(II), Cr(III), Cu(II) and Ni(II) from aqueous sample solution. It has been proved that using chromatographic columns packed with CELLPHOS for preconcentration and 1.0 mol 1 -1 HCl for elution the adsorbed analytes are quantitatively enriched. An enrichment factor of 20 (100 ml sample, 5 ml concentrate) was achieved by this separation procedure, which was applied to a series of water analyses (river, sea, bog water).
Keywords: Cellulose phosphate; Heavy metals; Preconcentration; Water analysis